The Role of the Trade Union within the Framework of Company Restructuring Processes - Edurne Terradillos Ormaetxea (Oñati Socio-Legal Series)
The aim of this study is to make a specific proposal regarding the capacity of trade unions to represent the interests of all workers in company restructuring operations. We will particularly refer to the case of companies that do not have workers’ representatives; when a restructuring is going to happen in a company, the Spanish Law requires a period of bargaining; and it is difficult to share that workers, in an individual point of view, can bargain in name of other workers; even if he/she has been elected for this occasion. The method used in this work is focussed in a comparison between the rules trade unions have to negotiate and the treatment of trade unions as representatives of workers in the field of the conflict and the strike.